Proceedings of the 22nd ACM SIGSOFT International Symposium on Foundations of Software Engineering 2014
DOI: 10.1145/2635868.2635880
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the characteristics of vulnerable code changes: an empirical study

Abstract: To focus the efforts of security experts, the goals of this empirical study are to analyze which security vulnerabilities can be discovered by code review, identify characteristics of vulnerable code changes, and identify characteristics of developers likely to introduce vulnerabilities. Using a three-stage manual and automated process, we analyzed 267,046 code review requests from 10 open source projects and identified 413 Vulnerable Code Changes (VCC). Some key results include: (1) code review can identify c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 43 publications
3
92
0
Order By: Relevance
“…Bosu et al [7] and Bosu [6] performed a study on the characteristics of vulnerable code changes. The study found that careful review should be done to modified files and that code changes are made often by less-experienced developers.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Bosu et al [7] and Bosu [6] performed a study on the characteristics of vulnerable code changes. The study found that careful review should be done to modified files and that code changes are made often by less-experienced developers.…”
Section: Related Workmentioning
confidence: 99%
“…There are extensive work on techniques, tools, and processes to develop a secure development process, including the development of secure software using the agile approach [5] and identification of characteristics of vulnerable code change [7]. This study enumerates the security aspects that the developers address when they modify their software.…”
Section: Impact Of the Studymentioning
confidence: 99%
“…al. analyzed the security vulnerabilities that could be discovered by code review, identified the characteristics of vulnerable code, and the developers that wrote it [18]. They found that the common types of identified vulnerabilities are buffer overflow and cross-site scripting.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, our focus is specific to the Android system for which there is scarce work in the literature of vulnerability prediction. Perhaps the most relevant work to ours is by Bosu et al [34] who studied the characteristics of vulnerable code changes. However, our study differs from it in the following three ways: a) we study changes that fix a vulnerability rather than ones that introduce it, b) we study known, severe and exploitable vulnerabilities rather than those found by code reviews and c) we aim at categorizing and describing the origin of the Android vulnerabilities and not generic changes that might indicate the introduction of one.…”
Section: Related Workmentioning
confidence: 99%